Structural and functional characterization of peste des petits ruminants virus coded hemagglutinin protein using various in-silico approaches - Gaur, Sharad Kumar; Chaudhary, Yash; Jain, Juhi; Singh, Rashmi; Kaul, Rajeev (Frontiers in Microbiology, 2024)
Peste des petits (PPR), a disease of socioeconomic importance has been a serious threat to small ruminants. The causative agent of this disease is PPR virus (PPRV) which belongs to the genus Morbillivirus. Hemagglutinin (H) is a PPRV coded transmembrane protein embedded in the viral envelope and plays a vital role in mediating the entry of virion particle into the cell. The infected host mounts an effective humoral response against H protein which is important for host to overcome the infection. In the present study, we have investigated structural, physiological and functional properties of Hemagglutinin protein using various computational tools. The sequence analysis and structure prediction analysis show that Hemagglutinin protein comprises of beta sheets as the predominant secondary structure, and may lack neuraminidase activity. PPRV-H consists of several important domains and motifs that form an essential scaffold which impart various critical roles to the protein. Comparative modeling predicted the protein to exist as a homo-tetramer that binds to its cognate cellular receptors. Certain amino acid substitutions identified by multiple sequence alignment were found to alter the predicted structure of the protein. PPRV-H through its predicted interaction with TLR-2 molecule may drive the expression of CD150 which could further propagate the virus into the host. Together, our study provides new insights into PPRV-H protein structure and its predicted functions.